The Impact of the Formation of Petroleum Fund Policy on the Sustainability of Oil and Gas Activities in Indonesia - Awaf Wirajaya; Nugroho Adi Sasongko; Helda Risman (CV. AFDIFAL MAJU BERKAH, 2024)
Business activities in the oil and gas sector certainly require high costs from upstream to downstream. From upstream to downstream of Indonesian oil and gas, the gap between production and consumption is getting wider, namely 616 thousand BOPD production and 1,471 MBOPD consumption and refinery capacity is still below the consumption figure, namely 1,151 million barrels per day. The need for high costs can be minimized by establishing a policy called the Petroleum Fund. This Petroleum Fund is taken from state revenues from the oil and gas sector for specific purposes to ensure the sustainability of oil and gas activities for future generations. Petroleum funds, especially in Indonesia, can be used for several important things such as investment capital on the upstream side to increase potential reserve status. On the downstream side, it can be used to increase refinery capacity so that fuel oil imports decrease. The fluctuating nature of oil prices is certainly a threat that must be overcome, this is anticipated by forming this policy so that fuel prices remain affordable for the public. Then efforts to reduce greenhouse gas emissions become an important thing that must be achieved by oil and gas companies as well as increasing human resource capacity in areas around the oil and gas industry.